Planning of Tigaras Dock in Simalungun Regency (With Organic Architecture Design Approach) - Nurlisa Ginting; Neny Wiyanti (Talenta Publisher, 2018)
Simalungun Regency is an autonomous region that has quite a wealth of natural resources that require maximum development. Tourism development in Simalungun Regency has a very significant and strategic meaning. A tourism sector is a mainstay plane that is expected to support the development of regional development. The tourism is also not free from the available facilities and infrastructure such as port as a means of transport inter-island liaison. The Tigaras Ferry pier is one of the existing ports to connect the Tigaras districts with Simanindo in Samosir District. Tigaras dock at this time not so noticed by the local government, but the area is an alternative port in the field as a liaison to the island of Samosir through Simanindo pier. Supporting infrastructure in the region is also inadequate. The arrangement of Tigaras and the design of dock terminal building and public place using organic theme then produce that connect the aspect of the outer and inner space. Buildings with the formation of a mass of course organic, as well as the public area that can attract visitors to be more environmentally conscious. Through this revitalization, the designer hopes to facilitate passengers or people who will cross to Samosir Island by using this Tigaras dock.